Características e fatores determinantes do uso de tela excessivo na primeira infância: abordagem populacional no Ceará - Cruz, Mírian Alexandre Amaral (2024)
Digital devices have become common items in the family environment. These devices are being introduced at an increasingly early age, however the use of these technologies requires limits, since excessive exposure to screens in children can lead to various consequences, from obesity to problems in child development. In Brazil, studies on factors associated with screen time by children in early childhood are still insufficient and there is a lack of data to promote early, more effective and economical interventions. This study aimed to identify the characteristics and factors associated with excessive screen use in early childhood children in the state of Ceará, a representative location in the Brazilian semi-arid region. To this end, a populationbased cross-sectional study was carried out using a sample from the 7th Ceará Maternal and Child Health Survey (PESMIC). The study included women of reproductive age and children aged between two and six years. The dependent variable was excessive screen time, defined as two or more hours a day, and the independent variables included characteristics of the child, the family and social adversities. The variables were treated using frequency calculations, the Chi-square test and multiple logistic regression. The final sample consisted of 1912 children, 74.1% of whom used screens excessively, with an average of 3 hours a day. The prevalence ratio of screen use increased by 8% (p<0.001) each year between the ages of 2 and 5. Living in an urban area was associated with a higher prevalence of 17% (p<0.001) and not attending nursery/school had a prevalence ratio of 1.13 (p<0.001). The factors associated with excessive screen use in early childhood were the child's age, area of residence, mothers' participation in the labor market and maternal level of education. The data produced by this study is uncommon in developing countries and can contribute to the creation and improvement of public policies for children's health.